Study Of The Acceleration Of Light In Vacuum - Monroy, Oscar (2021)
As a consequence of the study on the variation of the speed of light with time in the underlying vacuum of natural systems, the concept of acceleration of light arises. From the set of parametric equations that express the substrate or essential kinematics of the vacuum, it is obtained a formula that describes the acceleration of light as a function of time. Two possible opposite directions for the acceleration of light are observed; these directions are correlated with the two possible opposite directions of the local vector quantum. The vector quantum, as well as the acceleration of light, would have intrinsic uctuations. For small uctuations, two complementary quasi-equilibrium conditions are established, which would explain why light rays are perceived in a straight line in ordinary free space. Correlations are also deduced for the uctuations of the opposite vector quanta, as well as for the uctuations of the opposite acceleration vectors of light. Finally, it is shown that the winding of light rays in the underlying vacuum of a microscopic system is greater than the winding of light rays in the underlying vacuum of a macroscopic system.